Killing bridezilla - Levine, Laura, 1943- (Levine, Laura, 1943- Jaine Austen mystery., 2008)
Hired by her high school nemesis, Patti, to rewrite the ending of "Romeo and Juliet" for her wedding, Jaine Austen gets more than she had bargained for when Patti falls to her death from the balcony just before her big scene.